2022
DOI: 10.1038/s41598-022-12234-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of quantum dots as a buffer layer in CIGS solar cells: a comparative study

Abstract: Quantum bandgap buffer layers can improve sunlight absorption in the short wavelength region, hence improving the performance of CIGS solar cells. In this study, we use numerical modelling to determine the impact of various buffer layers' electrical characteristics on the performance of CIGS thin film photovoltaic devices, particularly, carrier concentration and the quantum effect. As well Ag2S buffer layer has been experimentally examined to fulfilment its effect in term of bulk and quantum bandgap. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Thus, this technique allowed better sub-monolayer coverage with a minimum particle aggregation. This helped in accurately controlling the size and spectral absorption properties of these QDs 3 . Some earlier reports showed that the semiconductor molecules such as CdS was a prospective buffer layer that could be employed as typical n-type heterojunction partners in current and upcoming thin-film PV devices due to its direct bandgap transition (Eg 2.4 eV), transparency, n-type conductivity, and a direct bandgap transition high electron affinity (4.2 eV) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this technique allowed better sub-monolayer coverage with a minimum particle aggregation. This helped in accurately controlling the size and spectral absorption properties of these QDs 3 . Some earlier reports showed that the semiconductor molecules such as CdS was a prospective buffer layer that could be employed as typical n-type heterojunction partners in current and upcoming thin-film PV devices due to its direct bandgap transition (Eg 2.4 eV), transparency, n-type conductivity, and a direct bandgap transition high electron affinity (4.2 eV) 4 .…”
Section: Introductionmentioning
confidence: 99%
“… 2 CdS is the most commonly implemented n-type buffer layer for thin-film solar cells with excellent performance. 3 As a buffer layer, for optimum minority carrier transport, CdS ought to be as thin as possible to ensure low series resistance, as a thicker film might reduce the Schottky barrier's effectiveness. Consequently to enhance the CdS conductivity, a specific process called doping is achieved by introducing impurities into the semiconductor crystal intentionally, which can be either acceptor or donor atoms in their crystalline lattice.…”
Section: Introductionmentioning
confidence: 99%
“…The doping concentration, also known as N D , is a crucial factor that affects the device performance . Nevertheless, in our particular instance, it seems that the variable is less.…”
Section: Resultsmentioning
confidence: 83%